Prevalence and contributing factors of job strain among crane operators in a port container terminal in Malaysia - Yakub, Nor Wahida; Mohd Sidik, Sherina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
The information on job strain among crane operators in Malaysia is lacking. The aim of this study was to determine the prevalence and contributing factors of job strain among crane operators working in port container terminals. A cross sectional study was carried out at a port container terminal in Malaysia. Data was collected using validated self-administered questionnaires, which consisted of the Job Content Questionnaire (JCQ), and the Depression, Anxiety, and Stress Scale (DASS-21). All crane operators in the selected terminal participated in the study. Data was analyzed using SSPS version 19. Two-hundred-and-forty crane operators participated in the study. The prevalence of job strain determined from the JCQ was 43.8%. Job strain was significantly associated with psychological job demand, decision latitude, anxiety, physical isometric loads and muscle ache. The prevalence of job strain in this study was high. There is an urgent need to recognize the existence of this problem among crane operators by their respective management. Implementation of comprehensive stress management programs are recommended to reduce job strain among these workers.